Examination of Element Concentrations in Groundwater by ICP-MS for Monitoring of Pre-Earthquake Activities - Yaman, Mehmet; Sasmaz, Ahmet (Office Spectroscopy & Spectral Analysis, 2013)
This study presents the results of hydrogeochemical studies carried out in Zeytun thermal springs in Kahramanrnaras, located South Middle Anatolia-Turkey. More than 90 thermal water samples were collected on a regular basis from 2006 to 2008 to measure element concentrations as a monitor of earthquake precursors. Water samples were analyzed using ICP-MS. The observed B, Ba, Br and Ge concentrations for 16 months are in ranges of 79 similar to 422, 103 similar to 167, 28 similar to 93 and 0.3 similar to 1.2 mu g.L-1, respectively. Chloride concentrations for these periods are in range of 7 similar to 21 mg.L-1. The data identify some element anomalies before earthquakes. These anomalies are characterized by decreases up to 158% in Ba and Cl concentrations. The occurrence of these anomalies can be attributed to stress/strain induced pressure changes in the subsurface water systems. It can be suggested that the thermal springs in the fault line area are ideal sites for precursors of earthquakes.
Keywords: Earthquake; Groundwater; Elements; Precursory; ICP-MS